The Effect of Hydrogel Aloe vera (Aloe vera (L.) Burm) on the Number of Neutrophil Cells in Aggressive Periodontitis Induced by Aggregatibacter actinomycetemcomitans (In Vivo Study on Wistar Rats) - Chandra Susanto; Shieny Lokanata; Jeni Widya Ningrum (HM Publisher, 2021)
Introduction: Aggressive periodontitis is a periodontal disease that runs rapidly, characterized by gross alveolar bone loss, the disease is unprompted by complaints, not related to local aspects. Objective: The aim of this study was to determine the effect of Aloe vera hydrogel on the number of neutrophil cells in aggressive periodontitis induced by A. actinomycetemcomitans in Wistar rats. Methods: This type of research is a laboratory experimental design with post-test only design with control group design. This study used 24 Wistar rats divided into 6 groups, namely, negative control group (Basic hydrogel), ibuprofen and hydrogel Aloe vera 2.5%, 5%, 10%, 20%. Results: The test results for the mean number of neutrophil cells in the hydrogel aloe vera group of 2.5%, 5%, 10%, 20%, ibuprofen, and negative controls were 120.50 ± 12.92, 78.25 ± 7.37, 47, 25 ± 4.03, 1.00 ± 0.82, 0.50 ± 0.58, and 217.25 ± 62.26. The results of the oneway Anova statistical test obtained p value = 0.001, which means that there is a difference in the number of neutrophils of Wistar rats in all treatment groups. Conclusion: The conclusion of this study there is the effect of giving hydrogel aloe vera a concentration of 2.5%, 5%, 10%, 20% with ibuprofen on Wistar rats induced by aggressive periodontitis.